Asymmetric synthesis of new antimalarial aminoquinolines through Sharpless aminohydroxylation. Issue 1 (15th January 2016) - Bentzinger, Guillaume; De Souza, Wesley; Mullié, Catherine; Agnamey, Patrice; Dassonville-Klimpt, Alexandra; Sonnet, Pascal
Graphical abstract: Abstract: Recently, the asymmetric synthesis and biological activity of ( R )- and ( S )-4-aminoquinolinemethanols 1 as mefloquine analogues were reported. Several compounds showed very promising antimalarial activity, in the nanomolar range, against Plasmodium falciparum 3D7 and W2. Enantiomers with an ( S )-absolute configuration were more active than their ( R )-counterparts by a factor ranging from 2 to 15-fold, according to the compound and the plasmodial strain considered. In continuation of our work, three novel series of enantiopure aminoquinolines 2a, 2b, and 3 were synthesized via an asymmetric aminohydroxylation reaction. These compounds were obtained in 2 or 4 steps from a common amidoalcohol key-intermediate 4 . They displayed IC50 values close to the micromolar against the two P. falciparum strains 3D7 and W2. The study of the structure–activity relationships allows us to better understand the importance of the substitution and of the stereochemistry at C11 and C12 position of the quinoline and gives tracks for the design of new compounds more active against the plasmodial strains. Abstract : ( S )-Benzyl (1-(2, 8-bis(trifluoromethyl)quinolin-4-yl)-2-hydroxyethyl)carbamate: C21 H16 F6 N2 O3 80% ee [ α ]D 20  = −28.9 ( c 0.1, MeOH) Source of chirality: Asymmetric Sharpless aminohydroxylation Absolute configuration: ( S ) Abstract : ( S )-Benzyl(1-(2, 8-bis(trifluoromethyl)quinolin-4-yl)-2-(( tert -butyldimethylsilyl)oxy)ethyl)carbamate: C27 H30 F6 N2 O3 Si 76% ee [ α ]D 20  = −7.8 ( c 0.1, MeOH) Source of chirality: ( S )-Benzyl (1-(2, 8-bis(trifluoromethyl)quinolin-4-yl)-2-hydroxyethyl)carbamate Absolute configuration: ( S ) Abstract : ( S )-1-(2, 8-Bis(trifluoromethyl)quinolin-4-yl)-2-(( tert -butyldimethylsilyl)oxy)ethan-amine: C19 H24 F6 N2 OSi 74% ee [ α ]D 20  = +37.8 ( c 0.1, MeOH) Source of chirality: ( S )-Benzyl(1-(2, 8-bis(trifluoromethyl)quinolin-4-yl)-2-(( tert -butyldimethylsilyl)oxy)ethyl)carbamate Absolute configuration: ( S ) Abstract : ( R )- N -(( S )-1-(2, 8-Bis(trifluoromethyl)quinolin-4-yl)-2-(( tert -butyldimethylsilyl)oxy)ethyl)-3, 3, 3-trifluoro-2-methoxy-2-phenylpropanamide: C29 H31 F9 N2 O3 Si [ α ]D 20  = +39.9 ( c 0.1, MeOH) Source of chirality: ( S )-1-(2, 8-Bis(trifluoromethyl)quinolin-4-yl)-2-(( tert -butyldimethylsilyl)oxy)ethan-amine Absolute configuration: ( R ), ( S ) Abstract : ( S )- N -(1-(2, 8-Bis(trifluoromethyl)quinolin-4-yl)-2-(( tert -butyldimethylsilyl)oxy)ethyl)pentan-1-amine: C24 H34 F6 N2 OSi 78% ee [ α ]D 20  = +30.7 ( c 0.1, MeOH) Source of chirality: ( S )-1-(2, 8-Bis(trifluoromethyl)quinolin-4-yl)-2-(( tert -butyldimethylsilyl)oxy)ethan-amine Absolute configuration: ( S ) Abstract : ( S )- N -(1-(2, 8-Bis(trifluoromethyl)quinolin-4-yl)-2-(( tert -butyldimethylsilyl)oxy)ethyl)heptan-1-amine: C26 H38 F6 N2 OSi 74% ee [ α ]D 20  = +18.0 ( c 0.1, MeOH) Source of chirality: ( S )-1-(2, 8-Bis(trifluoromethyl)quinolin-4-yl)-2-(( tert -butyldimethylsilyl)oxy)ethan-amine Absolute configuration: ( S ) Abstract : ( S )-2-(2, 8-Bis(trifluoromethyl)quinolin-4-yl)-2-(pentylamino)ethanol: C18 H20 F6 N2 O 86% ee [ α ]D 20  = +22.0 ( c 0.1, MeOH) Source of chirality: ( S )- N -(1-(2, 8-Bis(trifluoromethyl)quinolin-4-yl)-2-(( tert -butyldimethylsilyl)oxy)ethyl)pentan-1-amine Absolute configuration: ( S ) Abstract : ( S )-2-(2, 8-Bis(trifluoromethyl)quinolin-4-yl)-2-(heptylamino)ethanol: C20 H24 F6 N2 O 74% ee [ α ]D 20  = +25.6 ( c 0.1, MeOH) Source of chirality: ( S )- N -(1-(2, 8-Bis(trifluoromethyl)quinolin-4-yl)-2-(( tert -butyldimethylsilyl)oxy)ethyl)pentan-1-amine Absolute configuration: ( S ) Abstract : ( S )-2-((1-(2, 8-Bis(trifluoromethyl)quinolin-4-yl)-2-(pentyloxy)ethyl)imino)-1-phenylethanone: C26 H26 F6 N2 O3 64% ee [ α ]D 20  = −12.6 ( c 0.1, MeOH) Source of chirality: ( S )-Benzyl (1-(2, 8-bis(trifluoromethyl)quinolin-4-yl)-2-hydroxyethyl)carbamate Absolute configuration: ( S ) Abstract : ( S )-1-(2, 8-Bis(trifluoromethyl)quinolin-4-yl)-2-(pentyloxy)ethanamine: C18 H20 F6 N2 O 58% ee [ α ]D 20  = +28.1 ( c 0.1, MeOH) Source of chirality: ( S )-2-((1-(2, 8-Bis(trifluoromethyl)quinolin-4-yl)-2-(pentyloxy)ethyl)imino)-1-phenylethanone Absolute configuration: ( S )